Incidence of Gall Weevil, Pachyonyx quadridens Chev. (Coleoptera: Curculionidae) on Butea monosperma in Bundelkhand Region of India - Kumar, Veeresh; Shashank, P. R.; Devi, Salam Rita; Srivastava, Madhulika; Uthappa, A. R.; Chaturvedi, O. P. (Indian Forester, 2019)
No Abstract.